Regulamentação jurídica da nanotecnologia - Nolasco, Loreci Gottschalk (2016)
INTRODUCTION. Research on the nanotechnology jobs emerge as one of the most spectacular possibilities of science in the twenty-first century. With skills of building materials, devices and systems with atomic precision, nanotechnology promises to improve human skills, new industries and products, social outcomes and quality of life, with the potential to produce considerable economic-political-social-environmental and legal impacts. It is estimated that by 2020 will be moved globally about $ 3 trillion, with about 20% of all manufactured products in the world based to some extent, the use of nanotechnology and that all semicondutores sector and half of the pharmaceutical industry relies upon new materials; besides directly involved six million jobs. This is due to its incorporation into various existing technologies (physics, chemistry, biology, medicine, electronics etc.), the result of technological convergence with ability to create new forms of life, but with the possibility to increase the risk of unlimited and unmanageable, which would, if released, interact differently with living systems, causing surprising effects and unpredicted (which is not provided) or unpredictable (which is unable to be provided), and potentially more toxic than the same mass equivalent conventional and larger particles. Given the unpredictability of its results due to scientific uncertainties about the understanding of the risks related to the small size, area and surface chemistry, solubility and size, nanoparticles could cause disturbances in molecular and cellular levels. Similar in size to biological macromolecules such as proteins, DNA and phospholipids, have important consequences and can lift entirely unprecedented ethical principles in relation to other biotechnologies. Studies have reported potential toxicological effects of nanoparticles on human health result of interactions and biological, physical and chemical changes in various organic functional systems such as respiratory, digestive, nervous, lymphatic, excretory, blood circulation, skin, breast milk, muscle and placenta; as well as contamination of the environment. In the specific case study on the use of titanium dioxide nanoparticles in sunscreens, it was concluded by exposing both in professional environments or between the population groups and living organisms (biota), almost all phases of the lifecycle, and no exposure pathway can be dismissed as irrelevant to the workers. Nevertheless, is available for sale a quantity greater than 1,800 products and services of the most diverse, including medicines, cosmetics and foods containing nanomaterials and nanoparticles, and may expose the health and safety of consumers and workers globally to your process manufacturing and marketing. Because nanotechnology be able to act in a fundamentally different way compared to their respective material macro scale, it has been impossible to infer the safety of nanomaterials using the information derived from the bulk source material. In Brazil and almost the entire globe, there is no specific legislation with requirements of new and specific methods and assessment tools when a compound product of larger scale is replaced with the same compound nanoscale, getting health and safety aspects, and ethical, social and governance issues, short of nanotechnology development. Although there is no specific regulatory framework for the area where the products are registered in different countries, including Brazil, the respective regulatory agencies do it according to its type, in case-by-case basis, using normative applied generally to the chemicals, pharmaceuticals and cosmetics, even without any explicit reference to nanomaterials. Representatives of various organizations, governmental or not, and scientific groups, national and international express doubts about the ability of regulatory legislation, research standards and methods and conventional measurement strategies of non-specific toxicity applied to nanotechnology. GOALS. The specific aim of the thesis was to investigate whether the Brazilian legal system is (in) sufficient to specifically meet the technological innovations inherent in nanotechnology, with demands for creation of methodologies to identify, evaluate and manage the possible risks throughout the life cycle of nanomaterials and nanoparticles through prevention and precautionary instruments before placing on the market of products, services and processes that contain nanotechnology. It is understood that the legal regulations should also require the adoption of proper disposal of waste production measures, and to establish procedures for civil liability, criminal and administrative those involved, if applicable. The purpose of the legal regulation is to provide legal certainty for consumers and employees of present and future generations (prospective focus) and the environment. METHODOLOGY. The study had the scope to carry out exploratory and bibliographic research through survey data in the literature. Literature searches were performed by databases CAPES, is consulting with original and review articles on the subject Nanotechnology, Risk, Regulation; as well as specific books of Nanotechnology Area and Law. We also used the analytical method in the study of nanotechnology risks, the prospective liability, the precautionary principle and the analysis of the legislation. Based on the 1988 Federal Constitution, under the paradigm of democratic rule of law, the survey adopted the garantista theory and substantialist of law, which is based on the guarantee and direct application of fundamental rights, indicating that economic agents, companies and state should pay attention the mandamentais precepts of the Constitutional Charter and the infra-constitutional legislation, to at least achieve a standard of conduct that meets the dictates of fundamental rights, so it is possible to observe that economic development is not more important than human development, both one and the other, promises of converging technologies. RESULTS AND CONCLUSIONS. The advance of science, particularly in the sector of biology, genetic engineering, chemistry, medicine, biotechnology and nanotechnology, have imposed and continue to impose the state and the law, increased vigilance for possible risks and perpetráveis damage to physical and mental integrity human beings, so that scientific progress reconciles with the standards and tutelary principles of human personality, recognized and established in the 1988 Constitution, considered in the current democratic state paradigm of law, the center of the legal system. The Law as a science, through the establishment of legal instruments must create preventive and precautionary management measures for risk, based on the constitutional principles of information and accountability, the one that underlies the principle of focused caution for a time span (prospective) so far disregarded the law. In practice, in legal and constitutional terms, it implies the obligation to adopt appropriate safety and precautionary measures ordered and anticipatory (legislation, assessment tools and risk management), which limit or neutralize the causation of damage with a total irreversibility or generates partial effects negatively disturbing damage and imbalances of the decent survival of human life and all forms of life centered on the balance and stability of natural ecosystems or processed. Currently innovation in nanotechnology applications is proceeding ahead of regulatory policy, raising concerns that ethical, economic, legal, social, toxicological and environmental issues are delayed or lagged. These concerns challenge, globally, governments, manufacturers and civil organizations to establish a legal and judicial system that addresses new methods of management and monitoring of probable and some proven risks and damage during the production chain and post-marketing products and nanoparticles containing nanomaterials. New approaches must incorporate criteria of size, shape, surface area, activity and structure area, and require the construction of new detection tools, monitoring and adequate characterization of nanomaterials, as well as the understanding of processes occurring on the surface of nanoparticle when in contact with living systems in order to understand the possible toxicological effects, and therefore address the specificities of control and risk management throughout the production chain and life cycle of products and services with nanoparticles. Although exposures of workers, consumers and ecosystems contact applications and products containing nanomaterials are subject to a significant gravity context, putting workers at risk of exposure through inhalation, skin absorption or ingestion, and despite calls for moratorium on governments and atentassem industries to the problems generated by technologies convergence, the legal regulation of nanotechnology inched around the globe. Inobstante, concluded that reflex and partially by means of integrative interpretation of legis analogy, the Brazilian legal system provides regulations to nanotechnology, to identify responsibility, measurement of parameters, penalty and establishment of cautious conduct in dealings with the risk nanotechnology, in particular by establishing the precautionary principle, such as the Biosafety Law no. 11,105 / 2005 the National Policy on Solid Waste no. 12,305 / 2010; Nuclear Activities no. 6,453 / 1977, as well as judicial practice with the application of international treaties ratified by Brazil, before and after the enactment of the Brazilian Constitution of 1988, including, Agenda 21 (1992) and the Cartagena Protocol on Biosafety (2000) and the recourse to constitutional principles inspiring the juris analogy of the system, the principle of reasoned caution to the general safety requirement and full compensation of the damage, the preservation of human dignity, respect for life and health. Added to that, normative not legally binding (soft law) developed by economic organizations and international standardization (codes of conduct and responsibility) for the development, marketing and nanotechnology risk management, can complement the control regulation and state control. So that stakeholders in nanotechnology should take into consideration at the time committed efforts and resources in that sense some parameters to guide its activities and observe what they represent for their activity externalities of legal regulation. The research points principles and indicators that should be deployed as supervisory measures and preventive management of risks of nanotechnology and nanomaterials in order to ensure its safe development, among which stands out the precautionary approach and mandatory specific regulations. They also point out some strategic proposals for risk management, including controls in the workplace, volunteer programs and insurance. It concluded that the risk management for protection and promotion of research activity and its holders, as well as to preserve the quality of life of the human being and the environment in general, can be made at various levels, including government regulatory agencies the definition of environmental, health and safety, companies in the implementation of industrial management programs and hygiene products and insurers in the formulation of coverage policies and prices. It remains, however, the Brazilian legal challenge in specific regulatory and comprehensively nanotechnology or promote adaptation in particular the biosafety laws and solid waste for its proper disposal, involving the generation of new methodologies and protocols with a multidisciplinary approach, between principalmente chemistry, responsible for the synthesis, quantification and characterization of materials, biology and medicine, the design of the trials and interpretation of results in order to identify and evaluate systematically materials and safer alternative processes, and thus, anticipate the risks potential products and processes containing nanoparticles and nanomaterials, paying attention to the Federal Constitution of 1988 garantista bias, and head to the field of formulation, interpretation and application of laws, which binds all state powers (executive, legislative and judicial) , industries, scientists, laboratories, universities and other stakeholders in the development of nanotechnology, with purpose to ensure that the company will enjoy the economic and social benefits that nanotechnology promises widespread offer.